Realeconomik the hidden cause of the Great Recession (and how to avert the next one) - I͡Avlinskiĭ, G. (Grigoriĭ) (Yale University Press, 2011)
"This book directly confronts uncomfortable questions that many prefer to brush aside: if economists and other scholars, politicians, and business professionals understand the causes of economic crises, as they claim, then why do such damaging crises continue to occur? Can we trust business and intellectual elites who advocate the principles of Realpolitik and claim the "public good" as their priority, yet consistently favor maximization of profit over ethical issues? Former deputy prime minister of Russia Grigory Yavlinsky, an internationally respected free-market economist, makes a powerful case that the often-cited causes of global economic instability-institutional failings, wrong decisions by regulators, insufficient or incorrect information, and the like-are only secondary to a far more significant underlying cause: the failure to understand that universal social norms are essential to thriving businesses and social and economic progress. Yavlinsky explores the widespread disregard for moral values in business decisions and calls for restoration of principled behavior in politics and economic practices. The unwelcome alternative, he warns, will be a twenty-first-century global economy in the grip of unending crises"--